‘Un mare di parole’ tra "Assoli" e "Udunda Indina": Il plurilinguismo “malato” di Leo e Perla nella fase di rientro capitolino - Tamborrino, Matteo (Mimesis Journal, 2020)
This paper aims to reconstruct the two plays Assoli (1977) and Udunda Indina (1980), emblematic productions by Leo de Berardinis and Perla Peragallo, staged during the most daring phase of their research. Both characterized by an obsessive taste for the manipulation of idioms and for the shredding of meanings, the two theatrical performances – alongside the diagnostic and cathartic function of the word (ironically vilified among wordplays and puns) – bring to light the experimental potential of a very distinctive “teatro di parola”. These verbal phenomena, in terms of scenical praxis, reflect the intimate deconstructive project pursued, in those same years, not only by the two actors theirselves, but also by the wider framework of the so-called Italian “Nuovo Teatro”. The analysis is conducted on the basis of archival sources, direct testimonies, press clippings and, from a methodological point of view, by adopting studies of an interdisciplinary nature: both theatrical and linguistic.